2016
DOI: 10.1111/resp.12873
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of IL‐13‐induced periostin in airway epithelium attenuates cellular protein expression of MUC5AC

Abstract: Background and objective: Serum periostin is increased in asthma and serves as a surrogate marker for IL-13 activity in the lung. Serum levels of periostin are the most robust biomarker predicting a favourable response to the anti-IL-13 drug, lebrikizumab. We investigated the mechanisms of IL-13 stimulation of periostin, the polarized secretion of periostin and whether periostin would have a direct effect on mucin secretion by airway cells. Methods: Normal human bronchial epithelial (NHBE) cells were cultured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 40 publications
2
16
0
Order By: Relevance
“…Furthermore, STAT6 siRNA decreased periostin expression in lung fibroblasts [24]. Subsequently, the ERK1/2 pathway, as well as the JAK/STAT6 pathway, has also been shown to be important for periostin production in human airway epithelial cells cultured at an air-liquid interface [25] and in human lung fibroblasts [26]. Furthermore, other studies demonstrated that in vascular smooth muscle cells, the PI3K/Akt and ERK1/2 pathways, rather than the JAK/STAT6 pathway, are important for producing periostin [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, STAT6 siRNA decreased periostin expression in lung fibroblasts [24]. Subsequently, the ERK1/2 pathway, as well as the JAK/STAT6 pathway, has also been shown to be important for periostin production in human airway epithelial cells cultured at an air-liquid interface [25] and in human lung fibroblasts [26]. Furthermore, other studies demonstrated that in vascular smooth muscle cells, the PI3K/Akt and ERK1/2 pathways, rather than the JAK/STAT6 pathway, are important for producing periostin [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…81 Although inhibition of periostin attenuated IL-13-driven MUC5AC mucin production, periostin only weakly stimulated mucus secretion. 81…”
Section: Airway Inflammationmentioning
confidence: 96%
“…Furthermore, it was observed that simvastatin, a 3‐hydroxy‐3‐methylglutaryl coenzyme A (HMG‐CoA) reductase inhibitor, partially attenuated airway inflammation and reversed the overabundance of bronchial smooth muscle cells, thereby ameliorating AHR through an activated autophagic process in ovalbumin‐sensitized and ‐challenged murine models of asthma . Finally, Suzaki et al . investigated the use of a periostin‐neutralizing antibody in differentiated airway epithelial cells.…”
Section: Asthmamentioning
confidence: 99%
See 2 more Smart Citations